Pemanfaatan Refugia dengan Metode â€œBorder Plantâ€ Untuk Mengendalikan Hama Lalat Buah pada Tanaman Pare - Sarni Sarni; Helda Sabban (Universitas Khairun, 2022)
Fruit flies belong to pests that inflict huge losses on farmers, especially fruit and vegetable growers. Damage caused by this fruit fly causes the fruit to become rotten, several ways have been done to inflict fruit flies in Indonesia, but the use of pesticides is still dominant. other efforts are needed, namely by implementing Integrated Pest Management. One of them is ecosystem manipulation by planting using the